Identification of autophagy receptors for the Crohn’s disease-associated adherent-invasive Escherichia coli - Da Silva, Alison; Dalmasso, Guillaume; Larabi, Anaïs; Hoang, My Hanh Thi; Billard, Elisabeth; Barnich, Nicolas; Nguyen, Hang Thi Thu (Frontiers in Cellular and Infection Microbiology, 2024)
Crohn's disease (CD) is a chronic inflammatory bowel disease, of which the etiology involves genetic, environmental and microbial factors. Adherent-invasive Escherichia coli (AIEC) and polymorphisms in autophagy-related genes have been implicated in CD etiology.Autophagy is a key process for the maintenance of cellular homeostasis, which allows the degradation of damaged cytoplasmic components and pathogens via lysosome. We have shown that a functional autophagy is necessary for AIEC clearance. Here, we aimed at identifying the autophagy receptor(s) responsible to target AIEC to autophagy for degradation. We showed that, among the tested autophagy receptors (p62, NDP52, NBR1, TAX1BP1 and Optineurin), diminished expression of p62 or NDP52 increased the number of the clinical AIEC LF82 strain inside intestinal epithelial cells. This was associated with increased pro-inflammatory cytokine production. Moreover, p62 or NDP52 directly colocalized with AIEC LF82 and LC3, an autophagy marker. As the NDP52 Val248Ala polymorphism has been associated with increased CD susceptibility, we investigated its impact on AIEC control. However, in HeLa cell and under our experimental condition, no effect of this polymorphism neither on AIEC LF82 intracellular number nor on pro-inflammatory cytokine production was observed. Together, our results suggest that p62 and NDP52 act as autophagy receptors for AIEC recognition, controlling AIEC intracellular replication and inflammation.